EEG-based sympathy recognition. (1st January 2014) - Sadouni, Muhammad Ali; Gandomkar, Ziba; Arbabi, Ehsan
Expression and recognition of different emotions play important roles in human daily life. Among different emotions, recognising sympathy is one of the most complicated ones for humans. This paper presents an EEG-based sympathy recognition system using data collected from two channels, f3 and f4, in conventional 10–20 EEG system. Different visual stimuli have been shown to two subjects. A set of features have been extracted from the recorded EEG and each interval has been labelled as neutral or stimulated. The performances of k-nearest neighbour, artificial neural network and support vector machine in classifying data into two groups have been investigated. According to the result, the best correct classification rate was in average 97.05%. It has been also found that the alpha and the delta bands are more related to sympathy, comparing to the other frequency bands.